Translation and Identity - Da Silva Matte, Neusa (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1996)
AbstractThe author presents part of her research on translation theory and poetry. Her approach is based on two assumptions: 1) that translation is a process which extrapolates textual dimension; 2) that this process Can be tackled from the perspective of (textual) identity.